Pelvic floor dysfunction at transperineal ultrasound and chronic constipation in women with endometriosis. Issue 2 (24th January 2022) - Raimondo, Diego; Cocchi, Laura; Raffone, Antonio; Del Forno, Simona; Iodice, Raffaella; Maletta, Manuela; Aru, Anna Chiara; Salucci, Paolo; Ambrosio, Marco; Mollo, Antonio; Youssef, Aly; Casadio, Paolo; et al.
Abstract: Objective: To assess the association between sonographic findings at transperineal ultrasound (TPU) and chronic constipation (CC) in women with endometriosis. Methods: An observational prospective cohort study was performed by enrolling all women with endometriosis scheduled for surgery between September 2019 and October 2020. Women underwent TPU at rest and during Valsalva maneuver evaluating levator‐hiatal‐area (LHA), antero‐posterior diameter (APD), and levator ani muscle (LAM) coactivation. Ultrasound findings were compared between women with and without CC in the whole study population, and subsequently in two subgroups (only ovarian endometriosis and deep infiltrating endometriosis [DIE]). Results: In all, 87 women were enrolled: 29 (33%) with CC and 58 (67%) without CC. Women with endometriosis and CC showed a smaller LHA during Valsalva, less LHA and APD enlargement from rest to maximum Valsalva, and a higher prevalence of LAM coactivation compared with women without CC. In the ovarian subgroup, women with CC had smaller LHA at Valsalva, less enlargement of LHA and APD from rest to maximum Valsalva, and higher prevalence of LAM coactivation compared with non‐CC patients. In the DIE subgroup, TPU did not significantly differ between CC and non‐CC patients. Conclusion: TPU signs of pelvic floor muscle hypertonia are more frequent in endometriosis patients with CC compared with those without constipation, particularly in women affected by isolated ovarian endometriosis. Abstract : Women with endometriosis suffering from chronic constipation seem to have transperineal ultrasound signs of pelvic floor muscle hypertonia and coactivation.